The Dynamic Profiling of Serum Cytokine Networks Predicts Major Adverse Cardiac Events in ST-Elevation Myocardial Infarction: Serum Cytokine Networks Predicts Major Adverse Cardiac Even - Chen, Jun; Zheng, HuiPing (Journal of Medical Biochemistry, 2026)
Background: The inflammatory cascade following ST-elevation myocardial infarction (STEMI) involves complex cytokine interactions whose clinical utility remains undefined. We characterized the temporal dynamics of serum cytokine networks and their prognostic value for major adverse cardiac events (MACE).Methods: In this prospective observational study, 312 consecutive STEMI patients undergoing primary PCI were enrolled. Serial serum samples were obtained at admission (T0), 6 hours (T6), 24 hours (T24), and 72 hours (T72) post-PCI. A 15-plex cytokine panel was analyzed using high-sensitivity electrochemiluminescence. Patients were followed for 12 months for MACE (cardiac death, reinfarction, heart failure hospitalization).Results: Distinct cytokine trajectories were identified. IL-6 peaked earliest at T6 (median 34.2 pg/mL, IQR 18.7-52.1), while IL-8 peaked at T24 (22.4 pg/mL, IQR 15.3-31.8). Patients developing MACE (n=48, 15.4%) exhibited significantly higher IL-1β at T0 (3.2 vs 1.8 pg/mL, p
Keywords: acute myocardial infarction, cytokines, inflammation, prognosis, biomarkers